2018
DOI: 10.1093/rheumatology/key082
|View full text |Cite
|
Sign up to set email alerts
|

The effect of triple therapy on the mortality of catastrophic anti-phospholipid syndrome patients

Abstract: Triple therapy is independently associated with a higher survival rate among patients with CAPS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(51 citation statements)
references
References 10 publications
1
49
0
1
Order By: Relevance
“…Triple therapy use in CAPS is described in several studies, Rodríguez-Pintó et al study shows a statistical association between triple therapy and the decrease of mortality rate in patients with CAPS, when compared with other combinations or with none of the treatments included in triple therapy. [4] Although the case had a lethal outcome, the authors emphasize the use of triple therapy in CAPS and the challenge of treating patients with CAPS and infection where the balance between the need for anticoagulation, aggressive immunosuppression and infection control is difficult to manage.…”
Section: Discussionmentioning
confidence: 99%
“…Triple therapy use in CAPS is described in several studies, Rodríguez-Pintó et al study shows a statistical association between triple therapy and the decrease of mortality rate in patients with CAPS, when compared with other combinations or with none of the treatments included in triple therapy. [4] Although the case had a lethal outcome, the authors emphasize the use of triple therapy in CAPS and the challenge of treating patients with CAPS and infection where the balance between the need for anticoagulation, aggressive immunosuppression and infection control is difficult to manage.…”
Section: Discussionmentioning
confidence: 99%
“…The acute manifestations of CAPS are usually the result of an acute thrombotic microangiopathy. The differential diagnosis of CAPS in pregnancy and puerperium includes: disseminated intravascular coagulation (DIC), thrombotic thrombocytopaenic purpura (TTP), haemolytic-uraemic syndrome (HUS), heparin-induced thrombocytopaenia (HIT)7 and HELLP (haemolysis, elevated liver enzymes, low platelet count) syndrome, all of which can form part of the manifestations of CAPS. TTP and HUS are both characterised by thrombocytopaenia, macroangiopathic haemolytic anaemia and ischaemic organ damage.…”
Section: Discussionmentioning
confidence: 99%
“…Since triple combination therapy with anticoagulants, steroids and TPE and/or IVIG was first proposed in 2001, the prognosis of patients with CAPS has improved significantly. In fact, a recent report from the CAPS Registry confirmed that triple therapy is independently associated with a higher survival rate (mortality rate 28%) (Rodríguez‐Pintó et al , ). Patients who received both TPE and IVIG showed mortality rates similar to those who only received either (27·3% vs. 29%).…”
Section: Tpe In Autoimmune Haematological Disordersmentioning
confidence: 98%